State of African Languages Teaching and Learning in Higher Education in Kenya and South Africa - Khohliso, Xolani; Bwire, Adelheid Marie; Ngugi, Pamela; Miima, Florence Abuyeka; Babusa, Hamisi (Universitas Pendidikan Mandalika, 2024)
African languages have long been marginalized and underrepresented in higher education curricula, in Africa and globally. However, there is a growing recognition of the significance of African languages in academic settings, particularly as a means of preserving and promoting cultural heritage and facilitating communication and knowledge transfer among diverse communities. Studies have shown that language plays a critical role in shaping individuals' identities and their ability to access and engage with education. Therefore, there is a dire need for inclusion of African languages in higher education curricula to promote cultural diversity and equity in education. The use of African languages can enhance the relevance and impact of academic research and facilitate greater community participation in educational programmes. This article critically analyses the status of teaching and learning African languages in 2 institutions of higher education in Kenya and South Africa. It adopted a qualitative methodology and comparative case study as a design. It generated data through documents analysis . The study revealed that the two countries are not at the same level in implementing African languages in their curriculum. Whereas universities in South Africa have African languages Programmes, the Universities in Kenya have no such programmes. Moreover, there are several challenges , including lack of resources and infrastructure to support language instruction and research, as well as a need for greater support for African languages in academic institutions. This study, concludes that the significance of African languages in higher education curriculum cannot be overstated. By promoting linguistic diversity, cultural heritage, , and enhancing the relevance and impact of academic research, the inclusion of African languages in higher education curricula can contribute significantly to the advancement of knowledge and equity in education.